2017
DOI: 10.5812/zjrms.6187
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Cortisol in Patients with Acute Ischemic Stroke

Abstract: Background: Activation of the hypothalamo-pituitary-adrenal axis has been shown in acute ischemic stroke. Some recent studies suggest that serum cortisol level may have prognostic value in patients with ischemic stroke. The aim of this study was to evaluate the prognostic value of cortisol in patients with acute ischemic stroke. Methods: In this prospective observational study, 51 patients with acute ischemic stroke were evaluated. Cardioembolic and lacunar strokes were excluded. In the first 24 hours of admis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Several studies (Christensen et al., 2003; Iranmanesh et al., 2017; Kwon et al., 2015; Olsson et al., 1992; Zi & Shau, 2013) have focused on the negative impact of hypercortisolemia in poststroke recovery. A Chinese study (Zi & Shau, 2013) identifies cortisol as a significant prognostic marker of functional outcome and death poststroke.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Several studies (Christensen et al., 2003; Iranmanesh et al., 2017; Kwon et al., 2015; Olsson et al., 1992; Zi & Shau, 2013) have focused on the negative impact of hypercortisolemia in poststroke recovery. A Chinese study (Zi & Shau, 2013) identifies cortisol as a significant prognostic marker of functional outcome and death poststroke.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…The adverse cardiac effects also result from simultaneous sympathetic activation due to stress response. Some studies have shown no significant correlation between cortisol and ischemic stroke [ 5 , 13 , 14 , 15 ]. However, all of these studies involved a small number of patients, included patients with mild stroke severity only [ 15 ], or used sedatives concomitantly (midazolam or fentanyl), which may have caused variation in the results.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with acute IS, high serum cortisol at admission correlated with clinical severity according to NIHSS, as well as poor prognosis and functional outcome evaluated by the modified Rankin Scale [ 36 ]. In the majority of studies, cortisol levels were high in the first week after IS, and higher cortisol was associated with dependency, morbidity, depression, and mortality [ 37 ], though single studies demonstrated that, although IS was associated with a change in serum cortisol level, this change had no prognostic value [ 38 ]. In our study, comparative analysis of patients after IS and HC group revealed significantly elevated cortisol levels during the year after IS, starting from day 30 ( Figure 1 a), and persisting during the follow-up period ( Figure 3 a), though no significant changes in ACTH levels could be detected ( Figure 3 b).…”
Section: Discussionmentioning
confidence: 99%